Pengaruh Kualitas Informasi Akuntansi Dan Persepsi Kontrol Perilaku Terhadap Intensi Investor Dalam Pemilihan Saham - Putri Aisyah; Erinos N,R; Erly Mulyani (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to determine the effect of the quality of accounting information and perceptions of behavioral control on investor intentions in stock selection. The population of this study is the GI-IDX of Higher Education in the City of Padang. Samples taken based on purposive sampling technique using questionnaires as many as 100 respondents obtained by using Slovin formula. The method of analysis is done using Multiple Linear Regression Analysis. The results showed that the quality of accounting information has a positive and significant effect on investor intentions in stock selection and behavior control perceptions have a positive and significant effect on investor intentions in stock selection